High performance computer simulations of cardiac electrical function based on high resolution MRI datasets - Plotkowiak, M; Rodriguez, B; Plank, G; Schneider, J; Gavaghan, D; Kohl, P; Grau, V (2008)
In this paper, we present a set of applications that allow performance of electrophysiological simulations on individualized models generated using high-resolution MRI data of rabbit hearts. For this purpose, we propose a pipeline consisting of: extraction of significant structures from the images, generation of meshes, and application of an electrophysiological solver. In order to make it as useful as possible, we impose several requirements on the development of the pipeline. It has to be fast, aiming towards real time in the future. As much as possible, it must use non-commercial, freely available software (mostly open source). In order to verify the methodology, a set of high resolution MRI images of a rabbit heart is investigated and tested; results are presented in this work. © 2008 Springer-Verlag Berlin Heidelberg.